Activity‐Related Parenting Practices: Development of the Parenting Related to Activity Measure (PRAM) and Links with Mothers' Eating Psychopathology and Compulsive Exercise Beliefs. (6th November 2014) - Haycraft, Emma; Powell, Faye; Meyer, Caroline
Abstract This is a two‐study paper that developed a measure to assess parenting practices related to children's physical activity and explored maternal predictors of such parenting practices. Study 1: A self‐report measure of parents' activity‐related practices (the Parenting Related to Activity Measure) was developed, and a principal component analysis was carried out using data from 233 mothers of 4.5‐ to 9‐year‐old children. The results supported a six‐factor model and yielded the following subscales: Responsibility/monitoring; Activity regulation; Control of active behaviours; Overweight concern; Rewarding parenting; and Pressure to exercise. Study 2: Mothers (N = 170) completed the Parenting Related to Activity Measure, alongside measures of eating psychopathology and compulsive exercise, to identify predictors of activity‐related parenting practices. Mothers' eating psychopathology and exercise beliefs predicted activity parenting practices with their sons and daughters, but different predictors were seen for mothers of daughters versus sons. Mothers' eating and exercise attitudes are important predictors of their activity‐related parenting practices, particularly with girls. Identifying early interactions around activity/exercise could be important in preventing the development of problematic beliefs about exercise, which are often a key symptom of eating disorders. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.